The MCDM Technique is Being Utilized to Develop Sustainable Supply Chain Management in the Textile Industries - Ashish (International Journal of Industrial and Product Design Engineering, 2023)
Sustainable Supply Chain Management (SSCM) of production systems is crucial in the current globalization setting. Many businesses are having a lot of issues with supply chain management. In order to determine the most effective SSCM techniques, this research will rank the primary SSCM hurdles. The fuzzy analytical hierarchy process (FAHP) is used to rank the primary barriers in SSCM. A committee of three specialists was assembled to score various variables. Each specialist in the field of supply chain management had more than ten years of expertise. As the top three obstacles to system adoption in the textile sectors, a lack of top management support, a lack of SSCM project training and education, and a lack of strategic planning and implementation have all surfaced. The results suggest that for SSCM to be successful, senior management should be very supportive of various initiatives, training programs, etc. Organizations should work to increase the productivity of the textile industry generally. When developing an efficient SSCM system, professionals in the textile manufacturing industry will find these results to be of great value.
Keywords: FAHP; MCDM; Sustainable supply chain management; fuzzy SET